Chapter 10 The Multilingual Community Translation Classroom Challenges and Strategies to Train Profession-Ready Graduates - Lai, Miranda (Taylor & Francis, 2023)
Community translation is defined as the translation of different types of texts intended to facilitate communication between public services and people who do not have a good command of the mainstream language(s)" (Taibi & Ozolins, 2016, p. 7). It fulfils an important social role in multilingual and multicultural societies such as Australia, by facilitating and encouraging social, economic, and political participation. Community translators play a pivotal role in the diffusion of information produced by the government and other public agencies, as they make it possible for their communities to access high quality information in the language(s) they are proficient in. This chapter will showcase the pedagogical approaches and strategies employed by educators at RMIT University in Melbourne to offer community translation courses to students from more than a dozen language backgrounds, including some new and emerging languages. Such diversity has encouraged the educators to implement reflective and student-led pedagogical approaches to overcome the limitations of sourcing qualified teaching staff in some rare languages, as well as the set contact hours imposed by the institution. The aim of the training is to produce profession-ready graduates who are exposed to the realities of the industry before they graduate.